Building A Green Future: Green Budgeting as a Driver of Change - Timang, Vica Vanessa Sesaryo; Damayanti, Ratna Ayu; Kusumawati, Andi; ., Afdal (Journal of Posthumanism, 2025)
This study investigates the implementation of green budgeting to align fiscal policy with environmental sustainability at the subnational level, focusing on North Toraja Regency, Indonesia. Employing a mixed-method approach, the study combines content analysis of planning documents with SWOT (Strengths, Weaknesses, Opportunities, and Threats) and Analytical Hierarchy Process (AHP) analyses. Results reveal that while environmental goals are acknowledged in strategic plans, their practical implementation is limited due to the absence of regulatory frameworks, environmental performance indicators, and budget tagging systems. SWOT analysis places North Toraja in a moderate strategic position, highlighting both multi-agency involvement and institutional challenges. AHP identifies three priority strategies: establishing local regulations on green budgeting, enhancing performance-based reporting, and improving digital monitoring tools. The study offers a practical framework for local governments to strengthen green budgeting in decentralized contexts.